Essentiality of the Maltase AmlE in Maltose Utilization and Its Transcriptional Regulation by the Repressor AmlR in the Acarbose-Producing Bacterium Actinoplanes sp. SE50/110 - Schaffert, Lena; Schneiker-Bekel, Susanne; Dymek, Saskia; Droste, Julian; Persicke, Marcus; Busche, Tobias; Brandt, David; Pühler, Alfred; Kalinowski, Jörn (Frontiers in Microbiology, 2019)
Actinoplanes sp. SE50/110 is the wild type of industrial production strains of the fine-chemical acarbose (acarviosyl-maltose), which is used as α-glucosidase inhibitor in the treatment of type II diabetes. Although maltose is an important building block of acarbose, the maltose/maltodextrin metabolism has not been studied in Actinoplanes sp. SE50/110 yet. Bioinformatic analysis located a putative maltase gene amlE (ACSP50_2474, previously named malL (Wendler et al., 2015a)), in an operon with an upstream PurR/LacI-type transcriptional regulator gene, named amlR (ACSP50_2475), and a gene downstream (ACSP50_2473) encoding a GGDEF-EAL-domain-containing protein putatively involved in c-di-GMP signaling. Targeted gene deletion mutants of amlE and amlR were constructed by use of CRISPR/Cas9 technology. By growth experiments and functional assays of ∆amlE, we could show that AmlE is essential for maltose utilization in Actinoplanes sp. SE50/110. Neither a gene encoding a maltose phosphorylase (MalP) nor MalP enzyme activity were detected in the wild type. By this, the maltose/maltodextrin system appears to be fundamentally different from other described prokaryotic systems. By sequence similarity analysis and functional assays from the species Streptomyces lividans TK23, S. coelicolor A3(2) and S. glaucescens GLA.O, first hints for a widespread lack of MalP and presence of AmlE in the class Actinobacteria were given. Transcription of the aml operon is significantly repressed in the wild type when growing on glucose and repression is absent in an ∆amlR deletion mutant. Although AmlR apparently is a local transcriptional regulator of the aml operon, the ∆amlR strain shows severe growth inhibitions on glucose and – concomitantly – differential transcription of several genes of various functional classes. We ascribe these effects to ACSP50_2473, which is localized downstream of amlE and presumably involved in the metabolism of the second messenger c-di-GMP. It can be assumed, that maltose does not only represent the most important carbon source of Actinoplanes sp. SE50/110, but that its metabolism is coupled to the nucleotide messenger system of c-di-GMP.